Trans-catheter treatments of superior sinus venosus atrial septal defects. (June 2021) - Brancato, Federica; Rosenthal, Eric; Hansen, Jan; Duong, Phuoc; Jones, Matthew I.; Qureshi, Shakeel; Kabir, Saleha; Butera, Gianfranco
Abstract: Superior sinus venosus atrial septal defect is a communication between the two atria located above the upper margin of the oval fossa, immediately caudal to the junction of the superior vena cava and the right atrium. Commonly, it is associated with partial anomalous pulmonary venous drainage, particularly of the right upper pulmonary vein. Surgical repair has been the gold-standard approach to close this congenital anomaly, with excellent results. However, some recent studies have shown promising results from a trans-catheter approach by placing a covered stent in the superior vena cava to close the defect and redirect the anomalous pulmonary venous return posterior to the stent and into the left atrium. This procedure has proven effective and feasible in selected patients. Additionally, the development of a percutaneous approach has opened the possibility of treating patients with contraindications to surgical correction. Procedural planning using 3D printed models, simulation, holographic augmented reality, and interrogation of the superior vena cava with a balloon has made it possible to increase the effectiveness and safety of the transcatheter correction of this type of atrial septal defects. Based on our experience and literature data, transcatheter correction of sinus venosus atrial septal defect with partial anomalous pulmonary venous drainage may be an alternative to surgery in adult patients and would reduce the need for cardiopulmonary bypass. The short and medium-term results are promising, but longer follow-up studies on the use of this technique are needed to validate the procedure. Highlights: Superior sinus venosus atrial septal defect is a communication between the two atria and it is commonly associated with partial anomalous pulmonary venous drainage, particularly of the right upper pulmonary vein. Surgical repair has been the gold-standard approach with excellent results. We have developed a trans-catheter approach which consists in placing a covered stent in the superior vena cava to close the defect and redirect the anomalous pulmonary venous return posterior to the stent and into the left atrium. Procedural planning using 3D printed models, simulation, holographic augmented reality and interrogation of the superior vena cava with a balloon has are useful to perform the procedure. Based on our experience and literature data, transcatheter correction of sinus venosus atrial septal defect with partial anomalous pulmonary venous drainage may be an alternative to surgery in adult patients and would reduce the need for cardiopulmonary bypass.